2022
DOI: 10.1155/2022/6069060
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Fear of Disease Progression in Patients with Advanced Cancer and Usefulness of Dignity Therapy Intervention

Abstract: With changes in lifestyle and an increase in bad health habits, cancer has become a noncommunicable and frequently occurring disease that poses a serious threat to human life. Cancer is associated with high rates of morbidity and mortality worldwide. As a major negative life event, advanced malignancies lead to strong mood swings in most patients. Furthermore, various internal and external factors can have a huge impact on patients’ physical and mental health and put them in a stressful situation, causing a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…The included studies [15–41,46–49] involved 3471 participants from 14 distinct countries. The psychological interventions involved include AT, CBT, DT, FT, IPT, MT, PE, and ST.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies [15–41,46–49] involved 3471 participants from 14 distinct countries. The psychological interventions involved include AT, CBT, DT, FT, IPT, MT, PE, and ST.…”
Section: Resultsmentioning
confidence: 99%
“…Robertson, 2016 [37] UK FT UC 21/22 Prostate cancer HADS-A HADS-D ② Ren, 2018 [38] China CBT UC 98/196 Breast cancer HAM-A HAM-D ② Savard, 2006 [39] Canada CBT UC 25/20 Breast cancer HADS-A HADS-D ② Shari, 2020 [40] Malaysia CBT UC 32/30 Breast cancer HADS-A HADS-D ② Tang, 2021 [41] China MT UC 50/50 Lung cancer SAS Wu, 2018 [42] China PE UC 20/20 Breast cancer HADS-A HADS-D ② Xiao, 2022 [43] China DT PE 60/60 Lung cancer PHQ-9 Xu, 2019 [44] China MT UC 60/60 Cancer SAS/SDS ② Yuan, 2022 [45] China MT UC 40/40 Intracranial Tumor SAS/SDS ② Zhao, 2020 [46] China PE UC 50/51 Liver Cancer HADS-D Zahedian, 2021 [47] Iran CBT UC 12/12 Breast cancer BDI ② Zhang, 2022 [48] China DT UC 60/60 Cancer HADS-A HADS-D ② Zhu, 2023 [49] China…”
mentioning
confidence: 99%
“…Patients treated with DT compose a message to their loved ones through an interaction centred on nine questions, allowing them to regain their dignity and maintain it for generations to come. Effects such as increased hope [17] and decreased anxiety [18] have been observed, and patients have reported an increased sense of dignity after receiving DT [19][20][21]. Its effectiveness has been reported in patients with terminal cancer and it has been used worldwide as psychotherapy in palliative care [22][23][24].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Therefore, we suggest that health care staff develop targeted interventions based on positive psychology theories to increase patients' level of hope and reduce patients' FoP to improve their quality of life and subjective well-being. One study showed that dignity therapy can improve the hope level of cancer patients (Zhang et al, 2022b). Clinical medical staff should evaluate and identify patients with high levels of FoP early and provide psychological counseling referral services for these patients when necessary.…”
Section: The Relationship Between Hope and Fopmentioning
confidence: 99%